ENNEAGRAM IN BUSINESS: A NEW TOOL FOR MANAGING COMMUNICATION PROCESSES IN CONFLICT (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. Modernity shows that the most important factor in ensuring business competitiveness is its organizational culture. Conflicts cause significant damage to maintaining the team atmosphere in good condition, effective interaction in groups and cause loss of production resources and time. Modern managers must have a communicative technique for solving conflict situations with all their consequences without negatively affecting the organizational culture of the enterprise. The need to find new sources of managing communication processes in a conflict is extremely relevant and absolutely indisputable today. Enneagram is the key that will help to find an approach to each person and prevent the conflict from developing.The purpose of the article. Demonstrate enneagram as a tool for managing communication processes in conflict.Results. The essence of the enneagram as a detailed personality map - its strengths and weaknesses, needs, concerns and opportunities. Modern concepts of formation and basic methodological approaches to the use of the enneagram are described. Nine enneatypes are described and four main levels of using the enneagram by modern business organizations are highlighted. The value of the enneagram, which is the possibility to change the conflict dynamics for the better thanks to the vision of each employee's individuality, is determined. The features of the impact of the enneagram on the behavior of different categories of personnel in the organization are highlighted.Conclusiоns. Different types of management decisions require different information data. The Enneagram can become an effective tool for a manager in making managerial decisions, which, in turn, will increase business efficiency. The most important advantages of the enneagram are awareness of other people's peculiarities and the possibility to find a personal approach, to reveal the employee's potential, to motivate him/her correctly and to solve conflicts at early stages. Therefore, modern business organizations should pay more attention to the possibility of using enneagram as a tool for analysis and management of communication processes in a conflict to create a favorable atmosphere in the team, increase productivity and develop optimal solutions for complex conflict and crisis situations.
Keywords: enneagram, conflict, communication process, management, business